AB0460 Anca-positive vasculitis in systemic sclerosis: a tertiary referral center's experience. (23rd January 2014) - Damian, L.; Pamfil, C.; Petcu, A.; Tiburca, L.; Filipescu, I.; Ghib, L.; Rogojan, L.; Stancu, B.; Rednic, S.
Abstract : Background: The association of vasculitis and systemic sclerosis (SSc) is rare. The prevalence of ANCA-positive vasculitis in scleroderma is currently unknown. Objectives: To characterize the clinical features, associations and prognosis of ANCA- associated vasculitis occurring in SSc. Methods: Systematic retrospective analysis of all patients diagnosed with SSc in the Rheumatology Department, a tertiary referral center in Transylvania, over a 12-year period (2000 to 2012) using the hospital and outpatient database was employed. Epidemiological, clinical, laboratory and histology data were recorded. Patients with mixed connective tissue disease were excluded, as well as the ones with SSc and autoimmune liver disease with ANCA positivity and no clinical signs of vasculitis. Results: The charts of 126 SSc patients (86.9% F, 11%M) were analysed. Five cases of ANCA- associated vasculitis in SSc (3.96%) were identified, 3 M and 2 F, 4 limited and 1 diffuse SSc respectively, median age at vasculitis occurrence 63 yrs (30-75). The vasculitis occurred in 2 cases of previously known SSc (after 6 months and 2 years respectively), in 2 cases with previous Raynaud's phenomenon diagnosis was concomitant and in 1 patient preceded with 6 months the SSc diagnosis. The trigger was apparently infectious in 3 cases. The presenting vasculitic features were in all cases calf necrotic ulcerations, as well as digital ulcers in 2 cases. Overlapping large vessel vasculitis features (aortitis leading to aortic arch aneurysm) was noted in one patient. The biopsy revealed necrotizing vasculitis (4 cases), along with granuloma in the overlap case, leukocytoclastic vasculitis (1 case) and thrombosis (1 case). Complement consumption and pANCA positivity were seen in 4 patients; Scl-70 Ab were positive in 2 cases and anti-centromere antibodies in 2. Pulmonary involvement (ground-glass alveolitis) was noted in 3 cases, pulmonary hypertension in 3, mononeuritis multiplex and/or peripheral neuropathy in 3 and glomerulonephritis in 1. Secondary antiphospholipid syndrome was documented in 1 case. Of note, in one patient autoimmune liver dissease co-existed with leukocytoclastic vasculitis and pANCA positivity. Therapy consisted in cyclophosphamide and methylprednisolone pulses(3 cases) and azathioprine(1 case), antiaggregants and/or anticoagulation, with slow ulcer healing, renal and pulmonary improvement. However respiratory damage was present in all patients. Cutaneous vasculitis recurrence was noted in 1 patient after cyclophosphamide withdrawal. Conclusions: Vasculitis seemed to occur mainly in limited SSc and with a slight male predominance. It may point to presentation and diagnosis of SSc. The leg ulcer occurring in SSc may raise the possibility of ANCA- associated vasculitis. A thorough workup for organ involvement is required for an accurate diagnosis and proper treatment. References: Liang KP, Michet CJ: ANCA- associated vasculitis in scleroderma; a case series. Rheumatology Reports 2011; 3: e2 Kamen DL, Wigley FM, Brown AN: Antineutrophil cytoplasmic antibody-positive crescentic glomerulonephritis in scleroderma- a different kind of renal crisis. J Rheumatol 2006; 33: 1886-8. Disclosure of Interest: None Declared